International Conference on Dependable Systems and Networks, 2004 2004
DOI: 10.1109/dsn.2004.1311957
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the impact of faulty drivers on the robustness of the Linux kernel

Abstract: Drivers are becoming the larger part of operating systems kernels. Previous studies have shown that device drivers seem to be one of the most important sources of operating systems misbehavior. Their failure can have significant impact on the kernel and cause significant damages to the system as a whole. To objectively characterize the impact of faulty drivers, we have carried out a series of fault injection experiments. To conduct these experiments we have targeted the DPI (Driver Programming Interface) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…Similar to many other studies, e.g., [Albinet et al, 2004;Durães and Madeira, 2003], we model a monolithic system. The model consists of four layers: applications, OS, drivers and hardware platform.…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to many other studies, e.g., [Albinet et al, 2004;Durães and Madeira, 2003], we model a monolithic system. The model consists of four layers: applications, OS, drivers and hardware platform.…”
Section: System Modelmentioning
confidence: 99%
“…The work reported in [Albinet et al, 2004;Durães and Madeira, 2003;Gu et al, 2004;Jarboui et al, 2002a] explored the use of various error models and injection techniques for OS robustness evaluation and benchmarking. In [Jarboui et al, 2002a], for instance, error models similar to ours are used, but are injected at different levels within the Linux kernel.…”
Section: Other Contemporary Software Error Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most system administrators, users, and programmers still view them as an obscure and complex section of the operating system, which in part can be explained due to the DD necessity of addressing low level hardware details and OS internals. In the past, DD misbehavior has been pointed out as a prime cause for system crashes [3], and some researchers have showed that faults in DD can have a strong impact in the overall system dependability [4,5,6,7]. The recognized complexity associated with DD is aggravated as most vendors do not release openly the code, or even the hardware specifications.…”
Section: Introductionmentioning
confidence: 99%
“…Robustness testing and fuzzers are some approaches that study the system's ability in handling with erroneous input conditions at their interface [2,18,22]. Throughout the years, these approaches have evolved into more intelligent, and less random, vulnerability detectors [6,31,36].…”
Section: Related Workmentioning
confidence: 99%